Crystallography in the 21st century - Hasnain, S. Samar (International Union of Crystallography, 2015)

(untitled) (IUCrJ)
The field of crystallography, which has had a major impact on the sciences in the last 100 years, is continuing to expand scientific horizons as technical and conceptual boundaries are overcome. Structure–function–dynamics will become an integrated theme for many studies as will obtaining structures without the ‘benevolent tyranny’ of crystals.